A Novel Rotating Disk System for Disintegration of Excess Sludge - Ming yang Zhang; Yun Xiang; Jian wei Du (Journal of Chemistry)
Conventional activated sludge treatment process has been widely employed to deal with a variety of municipal and industrial waste water, but the production of sludge by this method is considerable. It is urgent to find an appropriate method which can solve this problem. Shear force produced by rotating disk system (a cell lysis system) was employed to break cell wall of sludge microorganism in order to release intracellular materials which can be reused as nutrient materials for metabolism of other sludge microorganisms in this study. Special feature on surfaces of disks had been proved to be a novel improvement which can improve disintegration effect apparently. Ultrasonic system can further promote minimization of excess sludge after treatment by rotating disk system in shorter time.